4CPS-067 Effectiveness and safety of the early switch from intravenous to oral antibiotics treatment in the pneumology ward. (March 2019) - Echeverria-Esnal, D; Martinez-Casanova, J; Dominguez-Alvarez, M; Estirado, C; Ausin, MP; Balcells, E; Martin-Ontiyuelo, C; Acin, P; Navarrete Rouco, E; Gea, J; Grau, S
Abstract : Background: The intravenous administration of antibiotics remains the route of choice at patient admission. Although the early-oral switch once the clinical stability has been achieved, has demonstrated to be effective and safe in other settings, its implementation in the pneumology ward has not been studied. Purpose: To assess the effectiveness and safety of an early-oral antimicrobial switch protocol in the pulmonology ward. Material and methods: Quasi-experimental study performed in a 400-bed tertiary hospital. The protocol was implemented in March 2018 and therefore two groups were identified: intervention group (March to August 2018) and control group (March to August 2017). All patients admitted to the pneumology ward were treated with intravenous antibiotics that, in turn, were available orally: therefore, amoxicillin/clavulanate, fluoroquinolones, trimethoprim-sulfamethoxazole, clindamycin and azithromycin were included. Results: A total of 200 patients were included. Main clinical outcomes are summarised in table 1 . Conclusion: The implementation of an early-oral antimicrobial switch protocol in the pneumology ward is effective and safe. The early-oral antibiotic switch could decrease the days of catheterisation and the potential related adverse outcomes, with a shortening in the length of stay. References and/or acknowledgements: None. No conflict of interest.